SOSIALISASI PENINGKATAN PEMAHAMAN DALAM MENGGUNAKAN MEDIA SOSIAL DENGAN BIJAK DI KALANGAN MASYARAKAT DI DESA SATRA, KECAMATAN KLUNGKUNG, KABUPATEN KLUNGKUNG - I.D.G.D. Sugama; I.K. Tjukup; I.P.R.A. Putra; D.G.P. Yustiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Today the use of communication technology is very rapid as well as the use of social media which has penetrated remote villages, technological developments that are open to modernity. With the presence of technology that is so fast, many people are not ready for this technological advancement, and many are not ready to use it properly such as the advancement of social media technology. It is necessary to carry out community service, about increasing public understanding in using social media properly and correctly. In this service, it is focused on several issues that have arisen, such as public knowledge of social media, the use of social media developments, public awareness of the negative impacts of using social media, and the way people respond to social media progress. This is deemed necessary in addition to supporting government programs in disseminating Law Number 11 of 2008 concerning Electronic Information and Transactions as well as providing understanding to the public as an effort to prevent crimes that utilize information technology and prevent the use of inappropriate and correct social media. This community service will be carried out by means of counseling and socialization with the target being village administrators, PKK, and the younger generation. Keywords : Improved, Understanding, Social Media